Learning from women - a training manual - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Women, conservation and agriculture : a manual for trainers 1992 199pp Pbk published by the Commonwealth Secretariat Marlborough House, Pall Mall London SW1Y 5HX, UK